Trends in hospitalizations of children with respiratory syncytial virus aged less than 1 year in Italy, from 2015 to 2019 - Renato Cutrera; Daniela d'Angela; Massimiliano Orso; Liliana Guadagni; Anna Chiara Vittucci; Ilaria Bertoldi; Barbara Polistena; Federico Spandonaro; Ciro Carrieri; Eva Agostina Montuori; Raffaella Iantomasi; Luigi Orfeo (BMC, 2024)
Abstract Background Respiratory syncytial virus (RSV) affects 60-80% of children below 1 year and it's the first cause of acute bronchiolitis. The aim of this study was to assess the trend and characteristics of hospitalizations for RSV infections in Italy. Methods This is a retrospective study based on the Italian Hospital Discharge Record (HDR) database. We analysed HDRs from June 2015 to May 2019, considering two groups of infants: Group 1 had a confirmed diagnosis of RSV; Group 2 had a diagnosis of acute bronchiolitis not RSV-coded. Results There were 67,746 overall hospitalizations (40.1% Group 1, and 59.9% Group 2). Hospitalization rate increased for Group 1 from 125 to 178 per 10,000 infants (+ 42.4%), and for Group 2 from 210 to 234 per 10,000 (+ 11.4%). The mean hospitalization length was 6.3 days in Group 1, longer than Group 2 (+ 1.0 day). A further analysis revealed that infants with heart disease or born premature had longer mean hospital stay compared to infants without risk factors (10.7 days versus 6.1 days, p < 0.0001; 34.0 days versus 6.1 days, p < 0.0001, respectively). Group 1 required more critical care (oxygen therapy and/or mechanical ventilation) than Group 2. We found that, in proportion to hospital admissions in pediatric and general hospitals, RSV was more frequently diagnosed in the first ones. The mean hospitalization cost increased for Group 1 (from € 2,483 to € 2,617) and Group 2 (from € 2,007 to € 2,180). Conclusions Our results confirmed that RSV pulmonary disease in infants is seasonal and often requires hospitalization. Our study suggested that RSV is responsible for an increasing hospitalization rate and related costs during the study period.